2020
DOI: 10.3892/etm.2020.9441
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibition sensitizes EGFR wild‑type NSCLC cell lines to erlotinib chemotherapy

Abstract: Tyrosine kinase inhibitors (TKIs) bring significant benefits for patients with cancers harboring epidermal growth factor receptor (EGFR) mutations. However, after treatment for a certain period, most patients ultimately acquire resistance. Numerous studies indicated that PI3K has an important role in tumor cell growth and drug sensitivity. Furthermore, inhibition of PI3K may lead to sensitization of non-small cell lung cancer (NSCLC) cells to EGFR-TKIs. The aim of the present study was to explore whether LY294… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…[ 22 ] PI3K‐AKT‐mTOR inhibition was also reported to sensitize lung cancer cells to or overcome resistance to EGFR‐TKIs. [ 30 , 31 , 32 , 33 , 34 , 35 ] BET inhibition was reported to delay the acquired resistance to anti‐EGFR antibody in head and neck squamous cell carcinoma, and synergize with anti‐HER2 TKIs in lung cancer and breast cancer. [ 36 , 37 , 38 ] The results showed that JQ1 and copanlisib combined with osimertinib led to significantly more potent inhibitory effect than using these drugs alone in BASC‐A tumoroids (Figure S4E , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] PI3K‐AKT‐mTOR inhibition was also reported to sensitize lung cancer cells to or overcome resistance to EGFR‐TKIs. [ 30 , 31 , 32 , 33 , 34 , 35 ] BET inhibition was reported to delay the acquired resistance to anti‐EGFR antibody in head and neck squamous cell carcinoma, and synergize with anti‐HER2 TKIs in lung cancer and breast cancer. [ 36 , 37 , 38 ] The results showed that JQ1 and copanlisib combined with osimertinib led to significantly more potent inhibitory effect than using these drugs alone in BASC‐A tumoroids (Figure S4E , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Further in vivo experiments demonstrated that LY294002 substantially circumvented resistance to gefitinib and promoted gefitinib-induced shrinkage of xenograft tumors on the basis of LPCAT1 knockdown. Of coincidence, the study by Zhou et al reported that LY294002 exerted the activity of sensitizing EGFR wild-type NSCLC cell lines to erlotinib chemotherapy [29]. These results strongly indicate that LPCAT1 can contribute to gefitinib resistance in LUAD by activating the EGFR/PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, in HPV-positive patients, those with PIK3CA mutations were recently found to have an increased chance of recurrence, and worse disease-free survival rates [25]. Preclinical studies have indicated that the dual inhibition of the PIK3CA and EGFR pathways demonstrates synergistic cell killing in head, neck [26] and lung cancer models [27].…”
Section: Discussionmentioning
confidence: 99%